Android-Based Bus Scheduling and Ticket Reservation System Using Round Robin - Hafiz, Muhammad; Harahap, Baginda; Syahputra, Dinur (PT. Technology Laboratories Indonesia (TechnoLabs), 2026)
Bus departure scheduling that is still carried out manually at PT Eldivo Tunas Arta often causes delays in information delivery and difficulties in managing operational schedules. This condition can affect the quality of service provided to customers and reduce the efficiency of company management. This study aims to design and implement an Android-based bus scheduling and ticket reservation system by applying the Round Robin algorithm. The Round Robin algorithm was chosen because it is capable of distributing departure schedules fairly and evenly among available bus fleets. The system development method used in this study is the System Development Life Cycle (SDLC), which consists of several stages including requirement analysis, system design, implementation, and testing. The results of this study show that the developed system can facilitate customers in accessing departure schedule information, booking bus tickets, and making digital payments more efficiently. In addition, from the management perspective, the system can reduce errors in schedule recording and improve operational efficiency. Therefore, the implementation of the Round Robin algorithm in the bus scheduling and ticket reservation system is proven to be effective in improving service quality and operational management of the company.